2012
DOI: 10.1088/1468-6996/13/2/023002
|View full text |Cite
|
Sign up to set email alerts
|

Surface science studies of metal hexaborides

Abstract: Over 30 years of surface science research on metal hexaborides are reviewed. Of this class of compounds, lanthanum hexaboride has been the subject of the majority of the studies because of its outstanding properties as a thermionic emitter. The use of LaB 6 cathodes as an electron source stems from the unusually low work function of ∼2.5 eV for the (100) surface combined with a low evaporation rate at high temperatures. Of particular interest has been the determination of the surface geometric and electronic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 95 publications
(163 reference statements)
2
42
0
Order By: Relevance
“…The surface termination of hexaborides has been systematically studied, motivated by the exceptionally low work function of LaB 6 and its use as a thermionic emitter [34]. LaB 6 has been found to be metal terminated [35], for SmB 6 partial or full Sm termination has been suggested [35,36].…”
Section: B Stoichiometrymentioning
confidence: 99%
“…The surface termination of hexaborides has been systematically studied, motivated by the exceptionally low work function of LaB 6 and its use as a thermionic emitter [34]. LaB 6 has been found to be metal terminated [35], for SmB 6 partial or full Sm termination has been suggested [35,36].…”
Section: B Stoichiometrymentioning
confidence: 99%
“…[16][17][18] Due to this reason, the topological nature arising from the intrinsic surface states is not easily confirmed experimentally. Another difficulty with SmB 6 is the strong correlation effect of f electrons.…”
Section: 15mentioning
confidence: 99%
“…It is generally accepted that for a promising thermionic cathode candidate, a smaller work function is indispensable to acquire a higher thermionic emission current density. 5,32 Meanwhile, abundant literature has reported that the work functions (Φ) of hexaborides are closely related to the indices of crystalline interfaces; the order of work functions for dif- 5,11,12,[33][34][35][36][37][38] In virtue of the GBPD results illustrated in Fig. 2a and 3a, it can be clearly observed that the most frequently occurring boundary planes are, successively, {001}, {011} and {111} planes, and boundaries are more frequently terminated by {001} planes rather than any other orientations.…”
Section: Discussionmentioning
confidence: 90%
“…8 Moreover, the size and types (energy, angle) of grain boundaries are significant to both the electron emission mechanism 9 and the carrier transport pathway; 10 with respect to the work function (defined as the minimum energy it takes for the electrons to be extracted from a metal), some theoretical studies suggest that substitution of lanthanum with barium atoms on the LaB 6 (100) surface could astonishingly reduce the work function to 1.43 eV. 11,12 With respect to the Richardson constant, it has been proven that such a constant could differ between either different emitting materials or various crystallographic faces of the same material. 13 In brief, to obtain an electron emissive material with higher performance, characterization of the occurrence frequency of boundary (including grain boundary and phase boundary) planes in the mixed LaB 6 structure is an important issue that should not be ignored.…”
Section: Introductionmentioning
confidence: 99%